Pension funds and FDI. Is there a link? - Brycz, Marcin; Kamińska, Teresa (Fundusze emerytalne a bezpośrednie inwestycje zagraniczne. Czy istnieje związek między nimi?, 2019)
The significant factors determining Foreign Direct Investments are trade openness, economic growth and the institutional profile of the country. Among the latter determinants, pension system privatization attracts foreign investors, as it gives them a signal that the country’s macroeconomic stability is going to improve. FDI are beneficial for economic development, especially for economies in transition. The question arises whether the degree of pension system privatization attracts FDI to developed economies. To answer this, Dunning’s Investment Development Path was applied for 44 countries over the period 2006-2016 from the OECD database. The first step consisted of clustering data to obtain the IDP stage for each country in a given year. The second step was a panel estimate. The outcome indicates that when a country is in a lower IDP stage (up to 2), the size of the private pension funds positively affects FDI inflow. When the country reaches the higher stage, private pension funds’ size does not seem to affect the FDI inflow
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 9, s. 18-31
Keywords: pension funds; FDI; Investment Development Path; panel data; fundusze emerytalne; BIZ; ścieżka rozwoju inwestycji; dane panelowe